A Feasibility Study on the Establishment of Smash Eat in Brittany Square, Fairview, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The Smash Eat was a snack bar that had a concept of anti-stress foods that were made into snacks. The researchers found it necessary to establish a business that offers anti –stress foods. In relation of preventing stress, the snack bar presented a “SmashRoom” where customers were free to let their stress come out for a moment by throwing plates on a large wall that Smash Eat provides for the said activity. In choosing healthy foods, they were actually influenced by their mood on a positive note, helping them be relived from tensions, stabilize blood sugar, and send stress packing. Researchers conducted a random survey to the people within the vicinity. The number of respondents on the random survey is 50. Through this survey, the researchers determined the opportunities and threat, the target market, the total demand and supply of the product. The proponents also conducted a survey according to the product, price, promotion and place. Survey were distributed and answered after which, they were collected by the researchers as a basis for the business proposal. Based on the data gathered, there was a big opportunity for the business to widen and made it viable in the market. The results of the survey gave a big possibility for the business to be a successful food industry. The product of the business and the twist of creating a room where customers can release their stress made the customers more interested. For this, the assurance of gaining a large amount of customers was more likely possible due to its location and the product itself.The Smash Eat is feasible and viable to the market and had a potential in the market growth in terms of marketing strategy, modern and economic status and financial security. Thus, social media such as facebook, Instagram andtwitter served as the first medium channel in promoting the product. Moreover, the business can double their business profit every year.
Keywords: smash eat, anti-stress foods, Brittany square, Fairview, Quezon City